Pengaturan Akad Mukhabarah bil Mudharabah dalam Kerja Sama Pertanian Tebu di Indonesia Perspektif Epistemologi - Susanti, Dyah Ochtorina; Putri, Auliya Safira (Jurnal Supremasi, 2024)
The mukhabarah bil mudharabah contract originates from a combination of two contracts, namely the mukhabarah contract and the mudharabah contract which are combined into one in the sugar cane farming partnership model. The formation of this contract is a new thing that is used as an effort to increase national sugar production by forming fair cooperation based on sharia contracts, however, the concept related to mukhabarah bil mudharabah contracts has not been concretely accommodated in statutory regulations, so this research aims to examine the regulation of mukhabarah bil mudharabah contracts in sugar cane farming partnership based on an epistemogical perspective. The research method used is normative juridical with a statutory and conceptual approach. The theory used is stufenbau theory. The results of this research indicate that at the meta-norm and grundnorm level there is already a legal basis for regulation regarding mukhabarah bil mudharabah contracts. The legal basis for regulating these contracts is also found at the level of Staatsfundamentalnorm norms and the level of Staatsgrundgezets norms, namely in the basic state regulations contained in Article 29 paragraph (2) of the 1945 Constitution, but at the next level there are only regulations regarding mudharabah contracts, while the mukhabarah contract has not been specifically regulated in the statutory regulations or other regulations below it.